Las Estatuas Galaico Lusitanas en posición de parada: I. Distribución espacial, emplazamientos y epigrafia asociada - Ríos González, Sergio (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2021)
The statues of warriors are one of the most prominent examples of the Castro culture in the northwest of the Iberian Peninsula. Notable in this category is a series of sculptures depicting the same iconographic motif: standing male, looking straight ahead, carrying a shield on the front. This paper, which is the first part of an integral research about this sculptures, studies their distribution and location as well as the inscriptions that are carved in some of them. Our analysis shows that these sculptural pieces are not found everywhere but in some specific sites within the old conventus bracarensis territory. Most of those locations are associated to heterogeneous settlements, but some others cannot be associated to inhabited areas. In this latter case, the sculptures could have been linked to key points in the territory (crossroads, hills, relevant piks, etc). Finally, engraved inscriptions seem concurrent with their corresponding sculptures, so this is a significant clue for the chronology of this unique statues of warriors.